ANALISIS SUMBER BELANJA PADA MUHAMMADIYAH AUSTRALIA COLLEGE - ROSYIDI, MUHAMAD YASIN ARIF; SUPRIYANTO , SUPRIYANTO; SUHARDI, MUHAMAD (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2024)
This research aims to describe and analyze what is the application of shopping sources at Muhammadiyah Autralia College in 2021-2022. The research method used in this research is library. That is, research whose data comes from literature reviews and other references that are relevant to this research. The results of this study found that, spending management at Muhammadiyah Australia College includes several components, namely: accouting and audit; advertising; amortization on operating lease right of use asset; bank fee; classroom; cleaning; consulting; depreciation; employee amenity; health and safety; insurance; interes expenses; IT expenses; legal expenses; light, power, heating; meeting; motor vehicle expenses; office expenses; open day; printing and stationery; repairs and maintenance; school event; subscriptions; superannuation; teaching materials; telephone and internet; training and development; wages and salary; and water. Analysis of the types of expenditure at Muhammadiyah Australia College on average experienced a significant increase in 2022. The report on the type of expenditure at Muhammadiyah Australia College from 2021 to 2022 experienced a fairly rapid increase, which amounted to AU$ 1,279,401. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan dan menganalisis apa saja penerapan sumber belanja pada Muhammadiyah Autralia College tahun 2021-2022. Metode penelitian yang digunakan dalam penelitian ini ialah Pustaka. Yaitu penelitian yang data-datanya berasal dari kajian literature dan rujukan-rujukan lainnya yang relevan dengan penelitian ini. Hasil penelitian ini menemukan bahwa, manajemen belanja pada Muhammadiyah Australia College mencakup beberapa komponen, yaitu: accouting and audit (akutansi dan audit); advertising (periklanan); amortisation on operating lease right of use asset; bank fee (biaya bank); classroom (kelas); cleaning (pembersihan); consulting (konsultasi); depresiation (depresiasi); employee aminities (fasilitas karyawan); health and safety; insurance (pertanggungan); interes expenses (beban bunga); IT expenses (biaya IT); legal expenses (biaya hukum); light, power, heating (cahaya, tenaga, pemanasan); meeting (pertemuan); motor vehicle expenses (biaya kendaraan bermotor); office expenses (pengeluaran kantor); open day (hari terbuka); printing and stationery (percetakan dan alat tulis); repairs and maintenance (perbaikan dan pemeliharaan); school event (acara sekolah); subscriptions (langganan); superannuation (pensiun); teaching materials (bahan ajar); telephone and internet (telepon dan internet); training and development (pelatihan dan pengembangan); wages and salary (upah dan gaji); water (air).